Geometrical behaviors of LRS bianchi type-I cosmological models. - Amirhashchi, Hassan; Zainuddin, Hishamuddin; Saz Dezfouli, Hamid Nil (Electronic Journal of Theoretical Physics, 2009)
By using Einstein’s theory of general relativity some properties of spatially homogeneous locally rotationally symmetric (LRS) Bianchi type-I space-time are investigated in empty space. The concept of Riemannian curvature tensor, Ricci tensor and Ricci scalar has been used to discuss the geometrical behavior of the space-time. It is shown that, LRS Bianchi type-I has always flat geometry in empty space. Also we have shown that the vacuum model does not have singularity when time goes to zero.